Znaczenie nadzwyczajnych kapituł generalnych w instytutach zakonnych : Meaning of extraordinary general chapters in religious institutes - SZEWCZUL , SZEWCZUL (Prawo Kanoniczne, 2019)
In relations to a an increasingly frequent convocations of general chapters in religious institutes of consecrated life, authoress took up a problem: if it is proper to take an excessive advantage of that institution? We expect, that participants of the extraordinary chapters will find proper ways of the renewal of religious life, solution of difficulties, and recovery from stagnation, and even – institute refound. It seems, that the meaning of the extraordinary chapters is frequently overestimated, expectations are too high and they are treated as very efficient and immediate antidote for problems existing in religious life, as well as for long-lasting negligence, wrong decisions, or their lack, performed by competent authority of the institute. Main contraindication related to the excessive using of that form of performing authority in the institute is a hasty convening of such chapters, risk of issuing too large number of the judiciary norms, or even the whole chapter’s documents, which, when cumulated, are very rarely read by institute members, and only few are saved. On the other hand the pre-chapter atmosphere in the institute, and during the chapter, brings about unfavourable, excessive, and long-term concentration of the members of the institute on certain matters, stirs up doubts, insecurity, needless discussions and pressure. Arrival of the chapter members to the place of proceedings – quite often from a distant countries - is connected with additional costs and a necessity of disruption of an institute everyday activities.